2001
DOI: 10.1054/bjoc.2001.2169
|View full text |Cite
|
Sign up to set email alerts
|

Biochemotherapy of metastatic malignant melanoma. Predictive value of tumour-infiltrating lymphocytes

Abstract: SummaryThe therapeutic efficacy of biochemotherapy in metastatic malignant melanoma still carries a low remission rate, but with some durable responses. It would therefore be of considerable importance if patients with a high probability of responding could be identified using predictive tests. The response to interferon-alpha (IFN-α) correlates with the occurrence of CD4 + lymphocytes identified by fine-needle aspirates from melanoma metastases (Håkansson et al, 1996). The present investigation studies a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In other studies, we have demonstrated that treatment with IFNa or IFNa in combination with cisplatin and DTIC results in early (incomplete) regression of metastases (Håkansson et al, 1996(Håkansson et al, , 2001. These responses showed a strong correlation with the amount of tumourinfiltrating CD4+ lymphocytes present before treatment.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In other studies, we have demonstrated that treatment with IFNa or IFNa in combination with cisplatin and DTIC results in early (incomplete) regression of metastases (Håkansson et al, 1996(Håkansson et al, , 2001. These responses showed a strong correlation with the amount of tumourinfiltrating CD4+ lymphocytes present before treatment.…”
Section: Discussionmentioning
confidence: 64%
“…However, objective remission following IFNa-based treatment is still only 15% (Legha, 1997). These observations suggest that an initial effective antitumour immune response is initiated following treatment, but that shortly thereafter immunological resistance occurs (Håkansson et al, 1999(Håkansson et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of tumor infiltrate has been associated with good [2] or poor [1] prognosis, nonetheless it is now understood that it is the nature and state of activation, rather than number of infiltrating cells that actually influences the outcome. When we evaluated B16F10 melanoma growth, tumor histology showed that the subcutaneously injected B16F10 cells formed a considerable tumor mass, presenting a clear borderline dividing between tumor and surrounding connective tissue containing abundant infiltrate by immune cells (Figure 1(a)), which was absent in the control thigh (sham treated) (Figure 1(b)).…”
Section: Tumor Growth Correlated Inversely With Infiltrate At the Tummentioning
confidence: 99%
“…Infiltration of immune effector cells occurs early in the course of tumor growth, and in some cases cell infiltration correlates with disease outcomes [1][2][3]. However, the immune system is not always able to circumvent tumor growth.…”
Section: Introductionmentioning
confidence: 99%